The NPY Family of Peptides in Immune Disorders, Inflammation, Angiogenesis, and Cancer - Zukowska, Zofia.; Zukowska, Zofia.; Feuerstein, Giora Z.; Feuerstein, Giora Z. (Progress in Inflammation Research, 2005)
Recent research indicates that the immune system and inflammatory reactions are governed and regulated by powerful neuronal mediators derived from the central and peripheral nervous system. The NPY family of peptides is a diverse group of neuropeptides that acts via multiple receptors, Y1-Y5, which are widespread not only in neurons but also in a variety of non-neural and immune cells. These peptides have been known as important regulators of many essential systems, such as blood pressure and cardiac function, food consumption and energy homeostasis. However, in recent years, they have also become recognized for their role as potent modulators of cell growth and immune functions with broad implications in chronic inflammatory diseases, cancer and angiogenesis. In this book, experts in the field analyze recent evidence supporting the role of NPY family of peptides in regulation of the immune/inflammatory system with special reference to its medical and therapeutic implications.